Heat Transfer to Liquid Hydrocarbons under Supercritical Bubble Boiling Conditions - A.A. Molokanov; W.X. Zhou; M.V. Kuzmin; S.A. Zhukov; N.A. Plishkin; L.S. Yanovskiy (Current Research Progress in Physical Science Vol. 7, 2025)
The study of heat transfer from heated surfaces to hydrocarbon mixtures has gained critical importance not only for energetic applications but also for its potential in medical therapies. Of particular interest are transient processes in hydrocarbon boiling, including regimes under supercritical bubble boiling (SBB) conditions. The unpredictable nature of these boiling modes makes it challenging to determine the heat transfer coefficients using conventional methods. This chapter presents data on heat transfer from a heated surface to hydrocarbon mixtures under convective, bubble, film, and supercritical bubble boiling regimes. The heat transfer process involves complex physicochemical phenomena, with hydrocarbon mixtures consisting of compounds with varying boiling points. During the heating of the surface, some low-boiling hydrocarbons evaporate, complicating the establishment of steady-state heat transfer. Furthermore, the presence of self-oscillations during heat transfer complicates the process.